Off-the-shelf, heparinized small diameter vascular graft limits acute thrombogenicity in a porcine model. (1st October 2022) - Elliott, Morgan B.; Matsushita, Hiroshi; Shen, Jessica; Yi, Jaeyoon; Inoue, Takahiro; Brady, Travis; Santhanam, Lakshmi; Mao, Hai-Quan; Hibino, Narutoshi; Gerecht, Sharon
Abstract: Thrombogenicity poses a challenge to the clinical translation of engineered grafts. Previously, small-diameter vascular grafts (sdVG) composed of fibrin hydrogel microfiber tubes (FMT) with an external poly(ε-caprolactone) (PCL) sheath supported long-term patency in mice. Towards the development of an sdVG with off-the-shelf availability, the FMT's shelf stability, scale-up, and successful conjugation of an antithrombotic drug to the fibrin scaffold are reported here. FMTs maintain mechanical stability and high-water retention after storage for one year in a freezer, in a refrigerator, or at room temperature. Low molecular weight heparin-conjugated fibrin scaffolds enabled local and sustained delivery during two weeks of enzymatic degradation. Upscaled fabrication of sdVGs provides natural biodegradable grafts with size and mechanics suitable for human application. Implantation in a carotid artery interposition porcine model exhibited no rupture with thrombi prevented in all heparinized sdVGs ( n  = 4) over 4–5 weeks. Remodeling of the sdVGs is demonstrated with endothelial cells on the luminal surface and initial formation of the medial layer by 4–5 weeks. However, neointimal hyperplasia at 4–5 weeks led to the stenosis and occlusion of most of the sdVGs, which must be resolved for future long-term in vivo assessments. The off-the-shelf, biodegradable heparinized fibrin sdVG layer limits acute thrombogenicity while mediating extensive neotissue formation as the PCL sheath maintains structural integrity. Statement of significance: To achieve clinical and commercial utility of small-diameter vascular grafts as arterial conduits, these devices must have off-the-shelf availability for emergency arterial bypass applications and be scaled to a size suitable for human applications. A serious impediment to clinical translation is thrombogenicity. Treatments have focused on long-term systemic drug therapy, which increases the patient's risk of bleeding complications, or coating grafts and stents with anti-coagulants, which minimally improves patient outcomes even when combined with dual anti-platelet therapy. We systematically modified the biomaterial properties to develop anticoagulant embedded, biodegradable grafts that maintain off-the-shelf availability, provide mechanical stability, and prevent clot formation through local drug delivery. Graphical abstract: Image, graphical abstract